Methods of Preparing of the Future Educators for Providing Succession of Teaching at Pre-School Establishments and Elementary School - Olha Novak (Pedagogical Discourse, 2013)
The author of the article considers using methods of preparing future educators for providing succession of teaching at pre-school establishments and elementary school in the process of studying the special course «Succession of teaching at pre-school establishments and primary school». Generalized scientific approaches to teaching methods and teaching methods are allocated according to the degree of independent thinking of students in mastering knowledge, commitment to training future educators to ensure continuity of learning in pre-school and elementary school. Methods are allocated on the basis of assessment of the creative activity of future teachers in the educational process: reproductive, problem teaching knowledge, partly retrieval and research methods.